CHARACTER-BASED MEDIA DEVELOPMENT OF LKS IN STUDENTS OF CLASS XI IPA SMA N 7 YOGYAKARTA ACADEMIC YEAR 2021/2022 - Sekar Mauladsih (CV. Fahr Publishing, 2023)
This study aims to determine: (1) the process of developing character-based LKS learning tools in history lessons in high school class XI with the ADDIE development model (2) Knowing the feasibility of the developed LKS, in terms of aspects of validity, practicality and effectiveness. This research is a research and development (Reserch and Development). The researcher developed a character-based LKS media device. The researcher uses the ADDIE development model using steps (Analysis, Design, Development, Implementation, and Evaluation). The results of this study indicate that: (1) This development research produces learning tools in the form of character-based worksheets. (2) The feasibility of the learning tools developed based on the results of the research is the learning tools developed are declared valid. The results of the material expert's assessment got a score of 4.1, the media expert's assessment got a score of 5. In terms of practicality, the learning tools developed were declared practical. Obtained through student and teacher response questionnaires, namely 4.16 for student responses and teacher responses of 4.31. The results of the observation of the implementation of learning show good criteria with a percentage of 80%; And in terms of effectiveness, the learning tools developed were declared effective based on student achievement tests with student learning completeness of 96.55%.